A dissolução da conjugalidade no Rio Grande do Sul (1965-2015) :história e relações de poder na transição do "até que a morte os separe" para "até que o mal-estar os divorcie" - Piva, Maristela (2020)
Family and marriage have always been in transformation. In the 20th century, the marital rupture, made possible by divorce, helped to give new contours to the family and to romantic arrangements. This study sought to make a historical analysis of the process of dissolution of conjugality in Rio Grande do Sul, especially in the Judicial District of Passo Fundo, with the period from 1965 to 2015 as a time frame. a peculiar way of dealing/confronting the issue of marital dissolution? What characterized the requests for marital dissolution? And how the representatives of the Law followed the evolution of Civil Law in their decisions? The method mixed qualitative and quantitative research, based on the assumptions of cultural history. The research sources included the documentary analysis of ten lawsuits related to the marital dissolution of the Passo Fundo district, from the decades of 1966 to 1975, 1976 to 1985, 1986 to 1995, 1996 to 2005 and 2006 to 2015. identify the actors, the motivations for the end of the marriage, the peculiarities and how the Judiciary responded to such requests. Five legal practitioners were also interviewed to identify what characterized the processes of dissolution of conjugality in RS over these fifty years. The interviews were submitted to Content Analysis. The data indicated that several changes took place in the family of Rio Grande do Sul and in the region of Passo Fundo, similar to what happened in the rest of Brazil after 1977. Divorce rates rose sharply. Families have reconstituted themselves, models of marriage have changed, women increasingly work outside the home, and the number of children among couples seeking divorce has declined. In the Passo Fundo region, this number is 1.1 children per couple, lower than the national average of 1.7 children per family, thus reflecting a demographic transition. The predominance of women was identified as the authors of marital dissolution processes in the Judicial District of Passo Fundo, making up 44% of the requests (in contrast to 14% of divorce requests sent by men, and 42% sent by mutual agreement by the couple ). The data demarcated the role of women in the decision to dissolve conjugality, a phenomenon similar to the rest of Brazil. There was a trend, over the decades, of women returning to using their maiden names after divorce (80% of cases between 2006 and 2015). But conflicting situations that demarcate gender issues remained: most women are still responsible for guarding their offspring, and domestic violence persists, affecting relationships, especially women. The opinion of the interviewees pointed to advances in Family Law, equaling the rights of men and women in the context of the marital relationship. The diversity of new marital arrangements was accepted, reassessing the notion of family beyond marriage. The "meanings" of marriage have changed. If in the past it was indissoluble, currently, personal, sexual fulfillment, complicity and happiness are sought in it. If such a search is not carried out, the marriage is easily undone, making no need to investigate the culprits. Divorce figures in contemporary family history and memories.